Depression and health-related quality of life in critical COVID-19 survivors. (1st June 2022) - Silva, J.; Martins, S.; Ferreira, A.R.; Fernandes, J.; Vieira, T.; Fontes, L.; Reis, N.; Braga, A.; Coimbra, I.; Paiva, J.A.; Fernandes, L.
Abstract : Introduction: Long-term neuropsychiatric consequences of critical illness are well known. Therefore, it is expected that critical COVID-19 patients might also present several psychiatric symptoms such as depression, with inevitable negative effect on health-related quality of life (HRQoL), commonly used as an indicator of illness and treatment impact. Objectives: To identify depressive symptoms in critical COVID-19 survivors and to examine its association with HRQoL domains. Methods: This preliminary study involved critical COVID-19 patients admitted into the Intensive Care Medicine Department (ICMD) of a University Hospital, between October and December of 2020. Patients with an ICMD length of stay (LoS)≤24h, terminal illness, major auditory loss, or inability to communicate at the follow-up time were excluded. From 1-2 months after discharge, all participants were evaluated by telephone at follow-up appointment, with Patient Health Questionnaire (PHQ-9) (depression) and EuroQol 5-dimension 5-level EQ-5D-5L (HRQoL). This study is part of the longitudinal MAPA project. Results: Eighty-three patients were included with a median age of 63 years (range: 31-86) and the majority were male (63%). The most reported problems on EQ-5D-5L domains were usual activities (82%) and mobility (76%). About 27% presented depressive symptoms, and with more problems of self-care (68%vs41%; p=0.029), pain/discomfort (86%vs49%; p=0.002), and anxiety/depression (96%vs54%; p<0.001). Conclusions: These preliminary results are in line in previous studies in critical COVID-19 survivors, with depression being associated with worse HRQoL. Bearing this in mind, follow-up approaches with an early screening and treatment of these psychiatric symptoms will be fundamental to optimize the recovery of these patients. Disclosure: No significant relationships.